Das Induktive Persönliche Abstandswarnsystem (IPA-14) als modernes Hilfsmittel zur Wendendurchführung im paralympischen Schwimmen - Wippich, A.; Stelling, G.; Hartmann, U. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Currently there are no possibilities or assistances for swimmers with visual handicap to get a better navigation in competition and training. Within a research project of the University of Leipzig in cooperation with the company Sportronic, a progressive feedback system for blind and visually impaired professional swimmers is going to be developed. The IPA-14, called Personal Inductive Distant Warning System has the intent and the task to improve the spatiotemporal orientation for the visual handicapped swimmers in pool and swimming lane. These swimmers should be given a new and better chance to use and increase their coordination skills as well as their physical abilities in water.